(untitled) (Global Journal of Medical Research, 2015)
Background: A smile is an important feature in determining an individual’s attractiveness. It is a simple concept that is seldom considered and often adjusted rather involuntarily. Objectives: A cross sectional study to assess the smile line in a sample of Sudanese population and its correlation with age, gender, and incisor classification. Material and methods: Clinical examination as well as a photograph was taken for 500 (230 males and 270 females) Sudanese adults with an age range of 15- >46 years in the Academy dental hospital to assess their smile line. Results: Low smile line was the most frequently (41%) encountered smile line followed by average (29.4%), high (22%), and the least being the very high smile line (7.6%). A statistically significant difference was found between age, gender and incisor classification in relation to the smile line (p value ≤0.05). Conclusion: Low smile line was the most frequent among Sudanese population and a strong correlation was found between the smile line and age, gender and incisor classification.